Social support and counselling as determinants of quality of life among secondary school adolescents with hearing impairment in Ibadan, Oyo State, Nigeria (2023)
Adolescents with hearing impairment experience grievous psychological and emotional problems due to their hearing defect, culminating in their poor quality of life. Earlier studies in this direction have not done much. This study, therefore, examined the influence of social support and counselling on the quality of life among secondary school adolescents with hearing impairment in Ibadan, utilising the descriptive survey research design of correlational type for carrying out the study, while the purposive sampling technique was used to select sixty (60) respondents. The instruments used were structured questionnaire tagged ‘Social Support and Counselling Questionnaire (r = 0.64) and Students with Hearing Impairment Quality of Life Questionnaire (0.86) while four research questions were answered. Data were analysed using descriptive statistics, Pearson Product Moment Correlation, Multiple Regression Analysis. Social support (r = 906*, p <0.05) and counselling (r = 368*, p < 0.05) were positively correlated with the quality of life of adolescents with hearing impairment. Social support and counselling predicted improved quality of life of adolescents with hearing impairment (F(2 57) = 226.583, p < 0.05) and accounted for about 89% of the total variance to the dependent variable. The relative contributions of the independent variables to the quality of life of adolescents with hearing impairment are as follows: social support (b = 0.874), and counselling (b = 0.261). Social support and counselling are important factors that influence the quality of life of adolescents with hearing impairment. Therefore, parents, teachers, government at all levels and other relevant stakeholders are enjoined to ensure adequate provision of social support and counselling to improve the quality of life of adolescents with hearing impairment.